A Comparative Study of Platelet Aggregation in Man and Laboratory Animals - Macmillan, D. C; SIM, A. K (Thrombosis and Haemostasis, 1970)
When some human platelets were aggregated in vitro by exogenous adenosine diphosphate (ADP) or adrenaline they released their own ADP. As ADP is the final stimulator of most aggregation, this ability to produce its own release gave a self- propagating secondary aggregation (SA) which could be marked in certain individuals and diseased states. In a survey of several animals, this ability to produce self- propagating aggregation was also found in a marked form in cats (which can form systemic platelet thrombo-emboli) and to a less extent in baboons and some dogs. This property of the platelets of humans and cats could be an important factor in their ability to form platelet thrombi more easily than other mammals. Thus, SA and its inhibition by drugs may be of considerable importance in the management of thromboembolic disease and a study of such agents carried out in these animals may be reasonably regarded as a relevant and useful preliminary to clinical trials in man.